Evaluasi Proses Bisnis Sistem Peminjaman Ruangan Online menggunakan Metode Quality Evaluation Framework (QEF) (Studi Kasus PT. Omah Pioner Ngalam) - Wildan Dery Rahadi; Buce Trias Hanggara; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
PT. Omah Pioner Ngalam or Ngalup Coworking Space is a company engaged in online space rental. The main business process running at Ngalup.co at this time is the process of borrowing space that runs online by consumers to companies. There are several problems with this online room borrowing system at Ngalup.co, among others, potential customers when they want to rent a room online still have to ask again regarding the implementation time available at Ngalup.co because there are several SOPs that have not been implemented by the party. company to enter data on which dates have been ordered by other customers. To be able to find out the current business process flow used the Busisneess Process Model (BPMN) method with the results of current business process modeling, then it is necessary to evaluate using a method, namely the Quality Evaluation Framework (QEF) with the results that there are three quality factors not in accordance with the code Q1, Q4, and Q9 and Root Cause Analysis (RCA) produces root causes that cause the business process to be obstructed.